2017
DOI: 10.1007/s11356-017-9449-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heavy metal contamination on oxidative stress of Eisenia andrei and bacterial community structure in Tunisian mine soil

Abstract: The aims of this work were firstly to study the effect of heavy metal-polluted soils from Tunisian mine on earthworm biochemical biomarkers and on bacterial communities and therefore to analyze the interaction between earth worms and bacterial communities in these contaminated soils. For this purpose, we had introduced earthworm Eisenia andrei in six soils: one from mine spoils and five from agricultural soils, establishing a gradient of contamination. The response of worms to the presence of heavy metal was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…For a correct assessment of soil contamination, the use of bioassays to quickly screen exposure and to show potential effects of contaminants is mandatory. Due to their life-style, earthworms are the first to be exposed to soils contaminants and, therefore, an environmental pollutant occurs earlier and their harmful effects are more evident than in other organisms [6,26,27]. To our knowledge, this is the first study that aims to investigate the effects of aloin exposure on DNA alterations in a species that is relevant to soil ecology.…”
Section: Discussionmentioning
confidence: 99%
“…For a correct assessment of soil contamination, the use of bioassays to quickly screen exposure and to show potential effects of contaminants is mandatory. Due to their life-style, earthworms are the first to be exposed to soils contaminants and, therefore, an environmental pollutant occurs earlier and their harmful effects are more evident than in other organisms [6,26,27]. To our knowledge, this is the first study that aims to investigate the effects of aloin exposure on DNA alterations in a species that is relevant to soil ecology.…”
Section: Discussionmentioning
confidence: 99%
“…corethrurus can probably reduce the mobile form of metal while increase its stable form in the rhizosphere (Lemtiri et al, 2016, Boughattas et al, 2017. Boughattas et al, (2018) justified the decrease of Pb concentration in Acacia biomass under earthworm treatment by the fact that earthworm can reduced the amount of Pb associated with the soluble and exchangeable fraction.…”
Section: P Corethrurus Earthworm and A Mangium Interaction On Phytomentioning
confidence: 98%
“…Previous studies have reported the interactive role of earthworms in improving plant growth in noncontaminated soils (Braga et al, 2016). In addition to this, the benefit effect of earthworms in the remediation of metal contaminated soil has been very well demonstrated in numerous research (Boughattas et al, 2017(Boughattas et al, , 2018Lv et al, 2016;Lemtiri et al, 2016), but only few studies have been conducted to assess their role in improving plant metal uptake during phytoremediation in contaminated soils (Kaur et al, 2017).…”
Section: P Corethrurus Earthworm and A Mangium Interaction On Phytomentioning
confidence: 99%
“…Sequential extraction is refers to the identification and quantification of the diverse distinct species, phases or forms that the metals occur [12]. It is sometimes referred to as Speciation, Fractionation or Selective extraction.…”
Section: Detailed Procedures Of Sequential Extractionmentioning
confidence: 99%